Lower-extremity dynamics of walking in neuropathic diabetic patients who wear a forefoot-offloading shoe. (December 2017) - Bus, Sicco A.; Maas, Josina C.; Otterman, Nicoline M.
Abstract: Background: A forefoot-offloading shoes has a negative-heel rocker outsole and is used to treat diabetic plantar forefoot ulcers, but its mechanisms of action and their association with offloading and gait stability are not sufficiently clear. Methods: Ten neuropathic diabetic patients were tested in a forefoot-offloading shoe and subsequently in a control shoe with no specific offloading construction, both worn on the right foot (control shoe on left), while walking at 1.2 m/s. 3D-instrumented gait analysis and simultaneous in-shoe plantar pressure measurements were used to explain the shoe's offloading efficacy and to define centre-of-pressure profiles and left-to-right symmetry in ankle joint dynamics (0–1, 1:maximum symmetry), as indicators for gait stability. Findings: Compared to the control shoe, peak forefoot pressures, vertical ground reaction force, plantar flexion angle, and ankle joint moment, all in terminal stance, and the proximal-to-distal centre-of-pressure trajectory were significantly reduced in the forefoot-offloading shoe ( P < 0.01). Peak ankle joint power was 51% lower in the forefoot-offloading shoe compared to the control shoe: 1.61 (0.35) versus 3.30 (0.84) W/kg (mean (SD), P < 0.001), and was significantly associated with forefoot peak pressure (R 2 = 0.72, P < 0.001). Left-to-right symmetry in the forefoot-offloading shoe was 0.39 for peak ankle joint power. Interpretation: By virtue to their negative-heel rocker-outsole design, forefoot-offloading shoes significantly alter a neuropathic diabetic patient's gait towards a reduced push-off power that explains the shoe's offloading efficacy. However, gait symmetry and stability are compromised, and may be factors in the low perceived walking discomfort and limited use of these shoes in clinical practice. Shoe modifications (e.g. less negative heel, a more cushioning insole) may resolve this trade-off between efficacy and usability. Highlights: Forefoot offloading shoes are used to treat plantar forefoot ulcers in diabetes. Its mechanisms of action and their effect on offloading and stability are unknown. A reduced push-off dynamics explains the offloading efficacy in these shoes. A left-to-right gait asymmetry and lower support base indicate gait instability. Resolving this efficacy-versus-usability trade-off may improve clinical acceptance.